Adult social work and high-risk domestic violence cases. (May 2018) - McLaughlin, Hugh; Robbins, Rachel; Bellamy, Claire; Banks, Concetta; Thackray, Debbie
Summary: This article focuses on adult social work's response in England to high-risk domestic violence cases and the role of adult social workers in multi-agency risk and assessment conferences. The research was undertaken between 2013 and 2014 and focused on one city in England and involved the research team attending multi-agency risk and assessment conferences. Interviews with 20 adult social workers, 24 multi-agency risk and assessment conferences attendees, 14 adult service users at time T1 (including follow-up interviews after six months, T2), focus groups with independent domestic violence advocates and Women's Aid and an interview with a Women's Aid service user. Findings: The findings suggest that although adult social workers accept the need to be involved in domestic violence cases they are uncertain of what their role is and are confused with the need to operate a parallel domestic violence and adult safeguarding approach, which is further, complicated by issues of mental capacity. Multi-agency risk and assessment conferences are identified as overburdened, under-represented meetings staffed by committed managers. However, they are in danger of becoming managerial processes neglecting the service users they are meant to protect. Applications: The article argues for a re-engagement of adult social workers with domestic violence that has increasingly become over identified with child protection. It also raises the issue whether multi-agency risk and assessment conferences remain fit for purpose and whether they still represent the best possible response to multi-agency coordination and practice in domestic violence.